Alterations in bacterial structure and function in seawater due to Mytilus coruscus farming: implications for sustainable aquaculture management - Wang, Fenglin; Gao, Lijia; Talma, Kobi; Pan, Yufeng; Liu, Qi; He, Yaodong; Peng, Zhengwei; Zhang, Xiumei (Frontiers in Microbiology, 2025)
Microorganisms are essential for maintaining the ecological balance and supporting the health of aquatic animals in aquaculture environments. This study utilized high-throughput sequencing technology to analyze the diversity, composition, co-occurrence networks, assembly mechanisms, and functional predictions of bacterial communities in seawater from both Mytilus coruscus aquaculture areas (AA) and non-aquaculture areas (NAA) across different seasons. The results indicated that the number of operational taxonomic units (OTUs) in the AA group was higher than the NAA group, while the Simpson index was significantly lower in the bottom water (p < 0.05). Additionally, the β-diversity (Bray–Curtis distance and βMNTD) was significantly reduced in the AA group compared to the NAA group (p < 0.05). M. coruscus farming influenced the relative abundance of certain genera, including Pseudoalteromonas, HIMB11, and Clade Ia, with the AA group exhibiting a greater number of specialist species. Co-occurrence network analysis revealed that the bacterial network in the NAA group had a higher number of nodes, edges, and modularity, whereas the AA group displayed greater closeness centrality and betweenness centrality. Following the removal of 80% of the nodes, the natural connectivity of the surface water in the AA group declined more rapidly than in the NAA group. Homogeneous selection was the primary assembly mechanism of bacterial communities in the AA group, while diffusion limitation was predominant in the NAA group. FAPROTAX functional predictions indicated the higher relative abundance of functions associated with organic matter degradation and nitrogen cycling in the AA group. These findings suggest that M. coruscus farming activities significantly alter the structure and function of bacterial communities in seawater, providing valuable data to support sustainable aquaculture for M. coruscus and optimize fisheries’ carbon sink management strategies.